Pemanfaatan Kotoran Manusia dan Arang Serbuk Gergaji sebagai Media Tanam Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pembibitan Awal - Yuliyanto .; Vira Irma Sari; Riki Safrizal (JURNAL CITRA WIDYA EDUKASI, 2017)
Nursery is the initial stage of palm oil plantation cultivation that results in the availability of superior seed with normal growth ready for planting in the field. Production of palm oil crops is highly dependent on the technical cultivation during the nursery. The activities of nursery should be considered to provide good quality seed suitable for cultivation. These activities include supervision, watering, weeding, fertilizing, consolidation and pest control. This research was conducted at Experimental Garden of Citra Widya Edukasi Polytechnic of Palm Oil, Bekasi, West Java. The aim of this research is to know the growth of morphology and physiology, to know the best mixed dose and to get the alternative of planting media for palm oil seed in the main nursery with the provision of human waste. The experimental design used was a complete randomized design of one factor, consisting of: A0: 100% human waste control; A1: 25% human waste: 75% sawdust ash; A2: 50% human waste: 50% sawdust ash; A3: 75% human waste: 25% sawdust ash; and A4: 100% control of sawdust ash. Each treatment was repeated twice, each treatment using two experimental samples so that for all there were 20 plants. The results showed that the provision of human waste significantly affect the growth of leaf number and leaf area, the best mixed dose with a ratio of 25%: 75% as an alternative to planting media in pre nursery of palm oil.